Design Thinking Law of Buying and Selling Inspiration of the Prophet's Hadith - Neneng Gina Agniawati; Tatang Zakariah (Gunung Djati Conference Series, 2021)
This study aims to discuss the inspiration for the hadith of the Prophet. in implementing the law of sale and purchase. This research method is qualitative through literature and field studies with the Islamic buying and selling law design thinking approach. The results and discussion of this research include the law of buying and selling and buying and selling innovations as well as the inspiration for the example of the Prophet. This research concludes that the hadith of the Prophet SAW. has inspirational messages in growing the creative economy of buying and selling law in Islam through innovative ideas with continuous testing precisely to seize a wide market.